Monovanadoped ruthenium-based pyrochlore structure water electrolysis catalysts, methods of making and applications
Patent Information
- Application Number
- CN202611123160.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明针对上述问题提出一种单钒掺杂钌基烧绿石结构电解水催化剂及制备方法和应用,其构思在于仅选用五水硫酸氧钒作为单一掺杂源,通过钒元素掺杂配合高温煅烧引入晶格缺陷,精准调控材料电子结构、增加表面活性位点,优化氧中间体吸附能,协同提升析氧催化活性与稳定性,简化原料体系,降低工艺调控难度
[0014]本发明产生的有益效果在于:采用溶胶 - 凝胶结合高温煅烧工艺制备钌基烧绿石复合催化剂,通过金属钒与晶格缺陷协同调控电子结构,有效降低析氧反应能垒。本发明制备工艺简单易操作、原料成本低、重复性好,为高效钌基析氧电催化剂的开发与工业化应用提供了新方向。
Smart Images

Figure CN123005437A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrocatalysis technology, and specifically relates to a vanadium-doped ruthenium-based pyrochlore structure water electrolysis catalyst, its preparation method, and its application. Background Technology
[0002] With the global energy crisis and environmental pollution becoming increasingly severe, the development of clean and sustainable energy has become an urgent need for social development. Hydrogen energy, as a high-calorific-value, zero-pollution green energy source, is considered an important direction for future energy structure transformation. Hydrogen production through water electrolysis can convert renewable energy sources such as solar and wind power into hydrogen energy, and is one of the key technologies for realizing the large-scale application of hydrogen energy. The water electrolysis process includes the cathode hydrogen evolution reaction and the anode oxygen evolution reaction. The oxygen evolution reaction (OER) is a four-electron transfer process with slow reaction kinetics and a high overpotential, which is the main bottleneck restricting the overall energy efficiency of water electrolysis. Therefore, a highly efficient electrocatalyst is needed to lower the reaction energy barrier.
[0003] Currently, commercial oxygen evolution catalysts are mainly iridium and ruthenium-based noble metal oxides. Among them, ruthenium-based materials are relatively inexpensive, have excellent catalytic activity, and have broad application prospects. Traditional RuO2 catalysts suffer from problems such as easy collapse of crystal structure, easy aggregation and loss of active components, and poor long-term operational stability. At the same time, single ruthenium-based oxides have poor tunability of electronic structure and low mass transfer efficiency, which cannot meet the requirements of industrial applications.
[0004] Pyrochlore oxides possess a unique three-dimensional porous structure, excellent electronic conductivity, and structural stability, making them ideal substrate materials for electrocatalysis. Current technologies often employ mixed doping with multiple metals such as cobalt, manganese, molybdenum, and vanadium. However, the doping mechanisms of these different metals vary significantly, making it difficult to uniformly control the preparation process and resulting in poor reproducibility in mass production. Summary of the Invention
[0005] This invention addresses the aforementioned problems by proposing a vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst, its preparation method, and its application. The concept lies in using only vanadium oxysulfate pentahydrate as a single dopant source. By introducing lattice defects through vanadium doping combined with high-temperature calcination, the electronic structure of the material is precisely controlled, surface active sites are increased, and the adsorption energy of oxygen intermediates is optimized. This synergistically enhances the catalytic activity and stability of oxygen evolution, simplifies the raw material system, and reduces the difficulty of process control.
[0006] In a first aspect, the present invention proposes a method for preparing a vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst, comprising the following steps: Step 1: Add yttrium nitrate hexahydrate and ruthenium trichloride trihydrate to deionized water, then add vanadium sulfate pentahydrate, citric acid and ethylene glycol; stir evenly, and carry out oil bath reaction at 80~120 ℃ until a gel is formed, and then vacuum dry at 100~120 ℃ to obtain the gel precursor; The molar ratio of ruthenium trichloride trihydrate to yttrium nitrate hexahydrate, vanadium sulfate pentahydrate, citric acid, and ethylene glycol is 1.0 : 0.6~0.95 : 0.03~0.2 : 1.5~3 : 1.8~3.6; Step 2: Grind the dried gel precursor thoroughly to pass through 150 mesh, and calcine it in air until a black solid is obtained. The calcination temperature is 700~1000 ℃, and the holding time is 3~6 h. Cool it naturally to room temperature to obtain the catalyst.
[0007] More specifically, the oil bath reaction time described in step one is 8-10 hours.
[0008] More specifically, the vacuum drying time described in step one is 4 to 8 hours.
[0009] More specifically, the calcination heating rate in step two is 2~10 ℃ / min.
[0010] More specifically, the calcination is carried out in a muffle furnace.
[0011] More specifically, the specific steps of the above preparation method are as follows: Step 1: Add yttrium nitrate hexahydrate and ruthenium trichloride trihydrate to deionized water, then add vanadium sulfate pentahydrate, citric acid and ethylene glycol; stir evenly, and carry out an oil bath reaction at 80~120 ℃ until a gel is formed; the oil bath reaction time is 8~10 h; vacuum dry to obtain the gel precursor, the vacuum drying temperature is 100~120 ℃, and the vacuum drying time is 4~8 h; The molar ratio of ruthenium trichloride trihydrate to yttrium nitrate hexahydrate, vanadium sulfate pentahydrate, citric acid, and ethylene glycol is 1.0 : 0.6~0.95 : 0.03~0.2 : 1.5~3 : 1.8~3.6; Step 2: Grind the dried gel precursor thoroughly to pass through 150 mesh, calcine it in air until a black solid is obtained, with a calcination heating rate of 5 ℃ / min; calcination temperature of 700~1000 ℃, holding time of 4h; and allow it to cool naturally to room temperature to obtain the catalyst.
[0012] Secondly, the present invention proposes a vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst prepared by the above-mentioned preparation method.
[0013] Thirdly, this invention proposes the application of the aforementioned vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst.
[0014] The beneficial effects of this invention are as follows: A ruthenium-based pyrochlore composite catalyst is prepared using a sol-gel combined high-temperature calcination process. By synergistically regulating the electronic structure through vanadium metal and lattice defects, the energy barrier of the oxygen evolution reaction is effectively reduced. The preparation process of this invention is simple and easy to operate, with low raw material costs and good reproducibility, providing a new direction for the development and industrial application of highly efficient ruthenium-based oxygen evolution electrocatalysts. Attached Figure Description
[0015] Figure 1 These are the XRD patterns of YVR-T calcined at different temperatures and synthesized pyrochlore YR in Examples 1-3 and Comparative Example 1 of the present invention.
[0016] Figure 2 shows the XRD patterns of YVR-x doped with different proportions of metallic vanadium and synthetic pyrochlore YR in Examples 4-6 and Comparative Example 1 of the present invention.
[0017] Figure 3 shows the OER polarization curves of Examples 4-6 and Comparative Example 1 of the present invention, with different proportions of vanadium metal YVR-x and synthetic pyrochlore YR under the condition of 0.5M H2SO4 electrolyte.
[0018] Figure 4a is a SEM image of the YVR-0.1 catalyst prepared in Example 4 of this invention.
[0019] Figure 4b This is a SEM image of the YVR-0.3 catalyst prepared in Example 5 of this invention.
[0020] Figure 4c This is a SEM image of the YVR-0.5 catalyst prepared in Example 6 of this invention.
[0021] Figure 4d This is a SEM image of the YR catalyst prepared in Comparative Example 1 of this invention. Detailed Implementation
[0022] Example 1
[0023] The preparation method and application of the three-dimensional composite water electrolysis catalyst based on ruthenium-based pyrochlore structure provided in this embodiment are as follows: (1) Weigh 0.1436 g of yttrium nitrate hexahydrate, 0.020375 g of vanadium sulfate pentahydrate and 0.130735 g of ruthenium trichloride trihydrate, add them to 10 mL of deionized water, and stir at room temperature for 30 min until the solids are completely dissolved; add 0.28818 g of citric acid and 0.1114 g of ethylene glycol to the solution, and continue stirring for 20 min until the mixture is homogeneous.
[0024] The mixed solution was placed in an oil bath at 90 °C and stirred at a constant temperature for 10 h until a viscous gel was formed. The gel was then placed in a vacuum drying oven and dried under vacuum at 100 °C for 8 h to obtain the gel precursor.
[0025] (2) The dried gel precursor was thoroughly ground to pass through 150 mesh, transferred to a muffle furnace, heated from room temperature to 700 ℃ at a heating rate of 2 ℃ / min, and calcined in air atmosphere for 4 h to obtain a black solid. It was then naturally cooled to room temperature to obtain the YVR-700 catalyst.
[0026] Example 2
[0027] The preparation method and application of the three-dimensional composite water electrolysis catalyst based on ruthenium-based pyrochlore structure provided in this embodiment are as follows: (1) Weigh 0.1436 g of yttrium nitrate hexahydrate, 0.020375 g of vanadium sulfate pentahydrate and 0.130735 g of ruthenium trichloride trihydrate, add them to 10 mL of deionized water, and stir at room temperature for 30 min until the solids are completely dissolved; add 0.28818 g of citric acid and 0.1114 g of ethylene glycol to the solution and continue stirring for 20 min until they are mixed evenly.
[0028] The mixed solution was placed in an oil bath at 80 °C and stirred at a constant temperature for 10 h until a viscous gel was formed. The gel was then placed in a vacuum drying oven and dried under vacuum at 110 °C for 6 h to obtain the gel precursor.
[0029] (2) The dried precursor was thoroughly ground to pass through 150 mesh, transferred to a muffle furnace, heated from room temperature to 800 ℃ at a heating rate of 5 ℃ / min, calcined in air atmosphere for 3 h, and naturally cooled to room temperature to obtain YVR-800 catalyst.
[0030] Example 3
[0031] The preparation method and application of the three-dimensional composite water electrolysis catalyst based on ruthenium-based pyrochlore structure provided in this embodiment are as follows: (1) Weigh 0.1436 g of yttrium nitrate hexahydrate, 0.020375 g of vanadium sulfate pentahydrate and 0.130735 g of ruthenium trichloride trihydrate, add them to 10 mL of deionized water, stir at room temperature for 30 min until the solid is completely dissolved, add 0.28818 g of citric acid and 0.1114 g of ethylene glycol to the solution, and continue stirring for 20 min until the mixture is homogeneous.
[0032] The mixed solution was placed in an oil bath at 120 °C and stirred at a constant temperature for 8 h until a viscous gel was formed. The gel was then placed in a vacuum drying oven and dried under vacuum at 120 °C for 4 h to obtain the gel precursor.
[0033] (2) The dried precursor was thoroughly ground to pass through 150 mesh, transferred to a muffle furnace, heated from room temperature to 1000 ℃ at a heating rate of 10 ℃ / min, calcined in air atmosphere for 6 h, and naturally cooled to room temperature to obtain YVR-1000 catalyst.
[0034] Example 4
[0035] The preparation method and application of the three-dimensional composite water electrolysis catalyst based on ruthenium-based pyrochlore structure provided in the examples are as follows: (1) Weigh 0.1819 g of yttrium nitrate hexahydrate, 0.0041 g of vanadium sulfate pentahydrate and 0.130735 g of ruthenium trichloride trihydrate, add them to 10 mL of deionized water, and stir at room temperature for 30 min until the solids are completely dissolved; add 0.1816 g of citric acid and 0.0724 g of ethylene glycol to the solution, and continue stirring for 20 min until the mixture is homogeneous.
[0036] The mixed solution was placed in an oil bath at 90 °C and stirred at a constant temperature for 10 h until a viscous gel was formed. The gel was then placed in a vacuum drying oven and dried under vacuum at 110 °C for 6 h to obtain the gel precursor.
[0037] (2) The dried precursor was thoroughly ground to pass through 150 mesh, transferred to a muffle furnace, heated from room temperature to 1000 ℃ at a heating rate of 5 ℃ / min, calcined in air atmosphere for 4 h, and naturally cooled to room temperature to obtain YVR-0.1 catalyst.
[0038] Example 5
[0039] The preparation method and application of the three-dimensional composite water electrolysis catalyst based on ruthenium-based pyrochlore structure provided in this embodiment are as follows: (1) Weigh 0.1627 g of yttrium nitrate hexahydrate, 0.0122 g of vanadium sulfate pentahydrate and 0.130735 g of ruthenium trichloride trihydrate, add them to 10 mL of deionized water, and stir at room temperature for 30 min until the solids are completely dissolved; add 0.2427 g of citric acid and 0.0947 g of ethylene glycol to the solution, and continue stirring for 20 min until the mixture is homogeneous.
[0040] The mixed solution was placed in an oil bath at 100 °C and stirred at a constant temperature for 8 h until a viscous gel was formed. The gel was then placed in a vacuum drying oven and dried under vacuum at 110 °C for 6 h to obtain the gel precursor.
[0041] (2) The dried precursor was thoroughly ground to pass through 150 mesh, transferred to a muffle furnace, heated from room temperature to 1000 ℃ at a heating rate of 5 ℃ / min, calcined in air atmosphere for 4 h, and naturally cooled to room temperature to obtain YVR-0.3 catalyst.
[0042] Example 6
[0043] The preparation method and application of the three-dimensional composite water electrolysis catalyst based on ruthenium-based pyrochlore structure provided in this embodiment are as follows: (1) Weigh 0.1436 g of yttrium nitrate hexahydrate, 0.0204 g of vanadium sulfate pentahydrate and 0.130735 g of ruthenium trichloride trihydrate, add them to 10 mL of deionized water, and stir at room temperature for 30 min until the solids are completely dissolved; add 0.28818 g of citric acid and 0.1114 g of ethylene glycol to the solution, and continue stirring for 20 min until the mixture is homogeneous.
[0044] The mixed solution was placed in an oil bath at 80 °C and stirred at a constant temperature for 10 h until a viscous gel was formed; the gel was then placed in a vacuum drying oven and dried under vacuum at 100 °C for 6 h to obtain the gel precursor.
[0045] (2) The dried precursor was thoroughly ground to pass through 150 mesh, transferred to a muffle furnace, heated from room temperature to 1000 ℃ at a heating rate of 5 ℃ / min, calcined in air atmosphere for 3 h, and naturally cooled to room temperature to obtain YVR-0.5 catalyst.
[0046] Comparative Example 1
[0047] The preparation method and application of the three-dimensional composite water electrolysis catalyst based on ruthenium-based pyrochlore structure provided in this embodiment are as follows: (1) Weigh 0.1915 g of yttrium nitrate hexahydrate and 0.130735 g of ruthenium trichloride trihydrate, add them to 10 mL of deionized water, and stir at room temperature for 30 min until the solids are completely dissolved; add 0.28818 g of citric acid and 0.1114 g of ethylene glycol to the solution, and continue stirring for 20 min until the mixture is homogeneous.
[0048] The mixed solution was placed in an oil bath at 80 °C and stirred at a constant temperature for 10 h until a viscous gel was formed. The gel was then placed in a vacuum drying oven and dried under vacuum at 110 °C for 6 h to remove organic components, thus obtaining a porous gel precursor.
[0049] (2) The dried precursor was thoroughly ground to pass through 150 mesh, transferred to a muffle furnace, heated from room temperature to 1000 ℃ at a heating rate of 5 ℃ / min, calcined in air atmosphere for 3 h, and naturally cooled to room temperature to obtain YR catalyst.
[0050] Take 5 mg of the final product obtained in Examples 1-6 and Comparative Example 1, 2 mg of Ketjen black, 490 μL of ethanol, 490 μL of deionized water and 20 μL of 5 wt% Nafion D520 dispersion respectively, and sonicate at 25 ℃ and 100 W for 2 h to prepare catalyst test ink.
[0051] 40 μL of test ink was added dropwise to the catalyst, which was then coated onto carbon paper as the working electrode. The reference electrode was an Ag / AgCl electrode, and the counter electrode was a graphite rod. The scan rate was set to 5 mV / s to complete the oxygen evolution performance test of the catalyst. Figure 3 The electrochemical polarization curves of YR prepared in this embodiment are compared with those of other YVR-0.3 examples. As can be seen from the figure, YVR-0.3 has the best performance.
[0052] Figure 1 , Figure 2 The XRD patterns of YVR prepared in this embodiment are shown in comparison with those prepared at other temperatures and with different doping concentrations. X-ray powder diffraction (XRD) was used to characterize the crystal structure and phase composition of the samples. The instrument was equipped with a Cu-Kα ray source (characteristic wavelengths λ1 = 1.5406 Å, λ2 = 1.5444 Å), with a working voltage of 40 kV and a working current of 40 mA. A step-scan mode was used for diffraction measurements, with a scanning range of 2θ = 10–80° and a step rate of 5° min⁻¹ to ensure accurate and comprehensive diffraction data acquisition. The experiment clarified the crystal structure characteristics and phase composition of the samples by analyzing their XRD patterns. Figure 1 shows the XRD patterns of samples prepared at different sintering temperatures. The product sintered at 700 ℃ showed no obvious sharp diffraction peaks, exhibiting amorphous characteristics. After heating to 800 ℃, the sample showed characteristic diffraction peaks of pyrochlore YR, indicating the beginning of crystal nucleation. At 1000 ℃, the diffraction peak intensity increased significantly, the full width at half maximum (FWHM) decreased, and the crystallinity significantly improved. The diffraction peaks of the pure-phase YR sample perfectly matched those of PDF#81-2340, indicating highly crystalline cubic pyrochlore. Figure 2 explores the effect of vanadium doping ratio on the phase composition. The main diffraction peaks of the YVR-0.1 and YVR-0.3 samples are consistent with the pyrochlore structure, and the slight shift in the diffraction peaks confirms that V has successfully doped into the lattice and induced lattice distortion. When the doping ratio is increased to 0.5, exceeding the lattice solid solution limit, excess vanadium and yttrium segregate, forming the YVO4 phase (PDF#17-0341). The comprehensive XRD results show that sintering temperature and vanadium doping amount jointly regulate the crystal phase structure of the material; suitable temperature and moderate V doping can introduce lattice distortion while maintaining the single-phase pyrochlore structure, while excessively high temperature or excessively high doping ratio will induce the precipitation of impurity phases.
[0053] Figure 4a-d shows the SEM images of the YR prepared in this embodiment compared to other YVR-0.3 examples. The microstructure of the samples was characterized using field emission scanning electron microscopy (FE-SEM). During sample preparation, the catalyst powder was dispersed and adhered to a conductive adhesive substrate, and the surface was sputtered with gold to improve conductivity. The electron beam acceleration voltage was set to 2-30 kV during the testing phase. SEM results showed that the undoped YR sample had a nanoparticle morphology. As the vanadium doping concentration increased, large-scale agglomeration of particles occurred, and the pore structure largely disappeared. These results indicate that an appropriate concentration of vanadium doping can effectively control the grain dispersion state of the pyrochlore catalyst. YVR-0.3 is the optimal doping ratio. Excessively high doping concentrations can induce particle agglomeration, which is detrimental to the acidic OER electrocatalytic process.
[0054] As can be seen from the above embodiments and comparative examples, this invention, through metal element doping combined with high-temperature calcination modification of ruthenium-based pyrochlore materials, can effectively regulate the electronic structure, increase active sites, accelerate charge transfer rate, and significantly improve the catalytic activity and stability of oxygen evolution reaction (OER). This preparation method is simple, the conditions are easily controlled, and it has strong reproducibility. The prepared catalyst has good application prospects in the field of oxygen evolution reaction in water electrolysis and is of great significance for promoting the industrial development of ruthenium-based electrocatalysts.
[0055] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications or equivalent variations made using the above technical content without departing from the scope of the present invention shall still fall within the scope of the present invention and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst, comprising the following steps: Step 1: Add yttrium nitrate hexahydrate and ruthenium trichloride trihydrate to deionized water, then add vanadium sulfate pentahydrate, citric acid and ethylene glycol; stir evenly, and carry out oil bath reaction at 80~120 ℃ until a gel is formed, and then vacuum dry at 100~120 ℃ to obtain the gel precursor; The molar ratio of ruthenium trichloride trihydrate to yttrium nitrate hexahydrate, vanadium sulfate pentahydrate, citric acid, and ethylene glycol is 1.0 : 0.6~0.95 : 0.03~0.2 : 1.5~3 : 1.8~3.6; Step 2: Grind the dried gel precursor thoroughly to pass through 150 mesh, and calcine it in air until a black solid is obtained. The calcination temperature is 700~1000 ℃, and the holding time is 3~6 h. Cool it naturally to room temperature to obtain the catalyst.
2. The preparation method of the vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst according to claim 1, characterized in that, The oil bath reaction time in step one is 8-10 hours.
3. The preparation method of the vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst according to claim 1, characterized in that, The vacuum drying time in step one is 4~8 hours.
4. The preparation method of the vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst according to claim 1, characterized in that, In step two, the calcination heating rate is 2~10 ℃ / min.
5. The method for preparing the three-dimensional composite water electrolysis catalyst with a vanadium-doped ruthenium-based pyrochlore structure according to claim 1, characterized in that, The calcination is carried out in a muffle furnace.
6. The preparation method of the vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst according to claim 1, comprising the following steps: Step 1: Add yttrium nitrate hexahydrate and ruthenium trichloride trihydrate to deionized water, then add vanadium sulfate pentahydrate, citric acid and ethylene glycol; stir evenly, and carry out an oil bath reaction at 80~120 ℃ until a gel is formed; the oil bath reaction time is 8~10 h; vacuum dry to obtain the gel precursor, the vacuum drying temperature is 100~120 ℃, and the vacuum drying time is 4~8 h; The molar ratio of ruthenium trichloride trihydrate to yttrium nitrate hexahydrate, vanadium sulfate pentahydrate, citric acid, and ethylene glycol is 1.0 : 0.6~0.95 : 0.03~0.2 : 1.5~3 : 1.8~3.6; Step 2: Grind the dried gel precursor thoroughly to pass through 150 mesh, calcine it in air until a black solid is obtained, with a calcination heating rate of 5 ℃ / min; calcination temperature of 700~1000 ℃, holding time of 4h; and allow it to cool naturally to room temperature to obtain the catalyst.
7. A vanadium-doped ruthenium-based pyrochlore-structured water electrolysis catalyst prepared by any of the preparation methods described in claims 1 to 6.
8. The application of the vanadium-doped ruthenium-based pyrochlore structured water electrolysis catalyst prepared according to claim 1 in the oxygen evolution reaction of water electrolysis in acidic electrolyte.
